2014
DOI: 10.1177/0269881114553646
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic stress on hippocampal adult neurogenesis and dendritic plasticity are reversed by selective MAO-A inhibition

Abstract: There is accumulating evidence that adult neurogenesis and dendritic plasticity in the hippocampus are neuroplastic phenomena, highly sensitive to the effects of chronic stress and treatment with most classes of antidepressant drugs, being involved in the onset and recovery from depression. However, the effects of antidepressants that act through the selective inhibition of monoamine oxidase subtype A (MAO-A) in these phenomena are still largely unknown. In the present study, adult neurogenesis and neuronal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 25 publications
7
31
0
1
Order By: Relevance
“…Consequently, M30 could prevent the varicosity formation and preserve the reduced spine density induced by CORT. Our findings are in agreement with previous observations that impaired dendritic plasticity induced by chronic stress could be rescued by MAO inhibitor [62]. Furthermore, soma size and volume were decreased by the CORT treatment, which could be attributed to the pathogenic processes of neuronal apoptosis when DNA is fragmented and chromatin are condensed [63].…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, M30 could prevent the varicosity formation and preserve the reduced spine density induced by CORT. Our findings are in agreement with previous observations that impaired dendritic plasticity induced by chronic stress could be rescued by MAO inhibitor [62]. Furthermore, soma size and volume were decreased by the CORT treatment, which could be attributed to the pathogenic processes of neuronal apoptosis when DNA is fragmented and chromatin are condensed [63].…”
Section: Discussionsupporting
confidence: 93%
“…These new neurons play a role in cognitive functions, such as acquisition and retention of memory (Mueller et al 2011). CMS has been shown to reduce cytogenesis in the ventral hippocampus, a specific portion of the hippocampus that encodes memories related to stress and emotions (Morais et al 2014). In the present study, we found that administration of piromelatine for 2 weeks significantly attenuated the CMS-induced decrease in the number of BrdUpositive cells in the hippocampus, suggesting that piromelatine increases hippocampal cytogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenesis which has been shown to be involved in cognitive impairment and depression in humans and in a variety of rodent models, is a function of serotonergic regulation and may affect the response to antidepressants in both cognitive and affective behavioral domains (Adeosun et al, 2014;Alenina and Klempin, 2015;Anacker, 2014;Biscaro et al, 2012;Braun and Jessberger, 2014;Chadwick et al, 2011;Cho et al, 2015;Dimitrov et al, 2014;Gundersen et al, 2013;Hill et al, 2015;Jiang et al, 2015;Lin and Wang, 2014;Mendez-David et al, 2013;Morais et al, 2014;O'Leary and Cryan, 2014;Parihar et al, 2013;Pereira Dias et al, 2014;Ransome et al, 2012;Rotheneichner et al, 2014;Schoenfeld and Cameron, 2015;Seib et al, 2013;Serafini et al, 2014;Shetty, 2014;Suarez-Pereira et al, 2015;Yau et al, 2014). In young adult mice, antidepressants increase stem cell proliferation (Hodes et al, 2010;Santarelli et al, 2003;Tanti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%